Thromboprophylaxis for varicose vein procedures – A national survey. (October 2019) - Boyle, Emily; Reid, Julie; O'Donnell, Mark; Harkin, Denis; Badger, Stephen
Background: Venous thromboembolism is rare following varicose vein ablation procedures, but uncertainty about its incidence combined with a lack of evidence-based clinical guidelines regarding thromboprophylaxis has led to debate about best practice. We conducted a national survey to investigate current practice among Irish vascular surgeons. Methods: An anonymous online questionnaire was emailed to all members of the Irish Association of Vascular Surgeons and the Northern Ireland Vascular Society. Results: Response rate was 60%. With regard to procedure type, 36.7% of respondents use only endovenous techniques and 53% use a combination of open and endovenous. Formal duplex imaging on all patients is obtained by 53.3%. With regard to VTE prevention, 73.3% always give thromboprophylaxis. For those who give it selectively, a variety of factors were considered as risks. Pharmacological agents used are enoxaparin in 73.3% of cases or tinzaparin, and 71.4% use a single dose (either 20/40 mg or 3500/4500 IU respectively). If patients are already taking anticoagulation, this is continued by 46.7% of respondents. Routine post procedure duplex imaging is carried out by 23.1% of recipients, either by the surgeon or formally and 80% review patients clinically. Moreover, 43.3% of respondents claim to know their post-operative VTE rate and this varies from 0 to 1% with one mortality reported. Conclusions: The majority of respondents use single-dose thromboprophylaxis periprocedurally for varicose vein ablation procedures. VTE rates are low but the true incidence may be unknown.